A Narrative Review on the Effects of Plasma-Rich Protein in Musculoskeletal Injuries: Insights into Inflammatory Markers, Growth Factors, and Healing - Daojing Su; Lu Chen; Kun Yang; Qinyuan Huangfu; Wang, Nan (Journal of the Pakistan Medical Association, 2024)
This narrative review was planned to explore the efficacy of plasma-rich protein in musculoskeletal injuries, emphasising its impact on inflammatory markers, growth factors and the healing process. Musculoskeletal disorders pose a significant global health concern, with the plasma-rich protein therapy emerging as a promising rehabilitative technique due to its potential to enhance healing. The therapy utilises the patients’ cells to stimulate growth, repair tissues, and modulate inflammation, offering a shift towards patient-friendly, non-hospitalised treatment. Through the modulation of inflammatory phases, stimulation of proliferative phases, and enhancement of remodelling phases, the plasma-rich protein therapy contributes to the expedited healing of musculoskeletal injuries. Clinical evidence supports its efficacy in reducing recovery time and managing pain, underscoring its therapeutic potential in musculoskeletal rehabilitation. Key Words: Plasma-rich protein, Musculoskeletal injuries, Inflammatory markers, Growth factors, Musculoskeletal healing.